An analytical study of the curve (force - time) and the relationship of the level of completion of the effectiveness of the payment of the timid applicants - Abdulkareem Hameed, Jamal; Abdulelah Salama, Omar; Nazim Alwan, Omar (International Journal of Psychosocial Rehabilitation, 2020)
Introduction, which was that the effectiveness of pushing the weight is one of the difficult arena and field activities in terms of technical performance, which depends on many Kinetic variables that we must continuously research to diagnose and develop them through field training, and by using modern techniques to analyze mechanical variables, including the use of the force measurement platform device (computer-linked foot scan) to extract kinetic variables (force-time) curve In order for the researcher, coach, and player to discover aspects of weakness and strength, then improve these variables and achieve the best levels in performance and achievement. Hence, the problem of research appears in studying the results of the action and reaction of force in the integration of kinetic performance by obtaining the appropriate acceleration during performance and its relationship to the most important related Kinetic variables Achievement, and the researcher’s hypothesis on the existence of a Statistically significant correlation between the kinetic variables and achievement in weight throwers The researcher claimed the existence of a statistically significant correlation between the kinetic variables and achievement of weight throwers. As for the research methodology, the researcher used the descriptive and analytical approach in the method of correlational relationships for the suitability and nature of the research problem. The sample was chosen in an intentional method consisting of 2 players for the effectiveness of throwing weight. In order to extract the studied variables by taking the best attempt for each player, the researcher used the statistical bag (SPSS) to extract the results. As for presenting the results, analyzing and discussing them, the significance of the differences was shown for the two indicators (strength and time) after comparing the value of (R) calculated with the table.